Response to brentuximab vedotin versus physician's choice by CD30 expression and large cell transformation status in patients with mycosis fungoides: An ALCANZA sub-analysis. (May 2021) - Kim, Youn H.; Prince, H. Miles; Whittaker, Sean; Horwitz, Steven M.; Duvic, Madeleine; Bechter, Oliver; Sanches, Jose A.; Stadler, Rudolf; Scarisbrick, Julia; Quaglino, Pietro; Zinzani, Pier Luigi; Wolter, Pascal; et al.
Abstract: Introduction: Mycosis fungoides (MF), the most common type of cutaneous T-cell lymphoma, can lead to disfiguring lesions, debilitating pruritus and frequent skin infections. This study assessed response to brentuximab vedotin in patients with MF in the phase III ALCANZA study. Methods: Baseline CD30 levels and large-cell transformation (LCT) status were centrally reviewed in patients with previously-treated CD30-positive MF using ≥2 skin biopsies obtained at screening; eligible patients required ≥1 biopsy with ≥10% CD30 expression. Patients were categorised as CD30min < 10% (≥1 biopsy with <10% CD30 expression), or CD30min ≥ 10% (all biopsies with ≥10% CD30 expression) and baseline LCT present or absent. Efficacy analyses were the proportion of patients with objective response lasting ≥4 months (ORR4) and progression-free survival (PFS). Results: Clinical activity with brentuximab vedotin was observed across all CD30 expression levels in patients with ≥1 biopsy showing ≥10% CD30 expression. Superior ORR4 was observed with brentuximab vedotin versus physician's choice in patients: with CD30min < 10% (40.9% versus 9.5%), with CD30min ≥ 10% (57.1% versus 10.3%), with LCT (64.7% versus 17.6%) and without LCT (38.7% versus 6.5%). Brentuximab vedotin improved median PFS versus physician's choice in patients: with CD30min < 10% (16.7 versus 2.3 months), with CD30min ≥ 10% (15.5 versus 3.9 months), with LCT (15.5 versus 2.8 months) and without LCT (16.1 versus 3.5 months). Safety profiles were generally comparable across subgroups. Conclusion: These exploratory analyses demonstrated that brentuximab vedotin improved rates of ORR4 and PFS versus physician's choice in patients with CD30-positive MF and ≥1 biopsy showing ≥10% CD30 expression, regardless of LCT status. Clinical trial registration: Clinicaltrials.gov, NCT01578499 . Highlights: Patients with mycosis fungoides (MF) have pruritic and infected skin lesions. Those with advanced-stage disease or large cell transformation have a poor prognosis. ALCANZA, a phase III study, showed a superior outcome of brentuximab vedotin (BV). This study assessed responses in the MF subset by CD30 or large cell transformation. BV was active regardless of baseline CD30 levels/large-cell transformation status.